"English is an unwritten rule here": Non-formalised language policies in multinational corporations. (3rd August 2018) - Sanden, Guro R.; Kankaanranta, Anne
Abstract : Purpose: The purpose of this paper is to examine the implications of corporate language policies that are implemented without formal decision-making processes. Design/methodology/approach: A qualitative case study based on three Scandinavian multinational corporations which use English as a common corporate language without formal language policy decisions. Findings: Non-formalised language policies are found to be clearly distinct from formalised language policies in terms of language policy format, language policy focus, language policy formation, language planning agency and management style. Non-formalised language policies can represent a type of informal control, but the absence of a policy document leaves employees without a common reference point which may cause confusion and inter-collegial conflict. Originality/value: The study offers a nuanced perspective on the role of language policies in corporate communication by demonstrating that language policies may come in a variety of different forms, also as implicit assumptions about language use. Findings reveal benefits and drawbacks of the different language policy approaches.